Coronally positioned flap with or without acellular dermal matrix graft in the treatment of class II gingival recession defects: A randomized controlled clinical study - Jagannathachary, Sunitha (Medknow Publications Pvt Ltd, 2010)
The aim of the randomized controlled single blind study is to evaluate the treatment of Miller's class II gingival recessions by coronally positioned flap (CPF) with or without acellular dermal matrix allograft (ADMA). Ten patients with 20 sites with maxillary bilateral Miller's class II facial recession defects were selected randomly into two groups of test (ADMA+CPF) and control (CPF alone) group with each group having 10 recession defects to be treated. The clinical parameters included plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), recession height (RH), recession width (RW), height of the keratinized tissue (HKT), and thickness of the keratinized tissue (TKT). These measurements were recorded at baseline and after 6 months post-surgery. Statistical analysis was made by the paired “t” test for intragroup and intergroup comparison was done by the unpaired “t” test. The percentage of root coverage for both the experimental and control groups were 82.2% and 50%, respectively. The changes from baseline to 6 months were significant in both the groups for PD, CAL, and RH; however, for parameters such as RW, HKT, and TKT significance was seen only in the experimental group. On comparison between two groups, only TKT showed statistically significance. It can be concluded that the amount of root coverage obtained with ADMA + CPF was superior compared to CPF alone.